A geometric morphometric analysis of hominin lower molars: Evolutionary implications and overview of postcanine dental variation. Issue 82 (May 2015) - Gómez-Robles, Aida; Bermúdez de Castro, José María; Martinón-Torres, María; Prado-Simón, Leyre; Arsuaga, Juan Luis
Abstract: Lower molars have been extensively studied in the context of hominin evolution using classic and geometric morphometric analyses, 2D and 3D approaches, evaluations of the external (outer enamel surface) and internal anatomy (dentine, pulp chamber, and radicular canals), and studies of the crown and root variation. In this study, we present a 2D geometric morphometric analysis of the crown anatomy of lower first, second, and third molars of a broad sample of hominins, including Pliocene and Lower, Middle, and Upper Pleistocene species coming from Africa, Asia, and Europe. We show that shape variability increases from first to second and third molars. While first molars tend to retain a relatively stable 5-cusped conformation throughout the hominin fossil record, second and third molars show marked distal reductions in later Homo species. This trend to distal reduction is similar to that observed in previous studies of premolars and upper second and third molars, and points to a correlated reduction of distal areas across the whole postcanine dentition. Results on lower molar variation, as well as on other postcanine teeth, show certain trends in European Pleistocene populations from the Atapuerca sites. Middle Pleistocene hominins from Sima de los Huesos show Neanderthal affinities and strong dental reduction, especially in the most distal molars. The degree of dental reduction in this population is stronger than that observed in classic Neanderthals. Homo antecessor hominins from Gran Dolina-TD6 have primitive lower teeth that contrast with their more derived upper teeth. The evolutionary implications of these dental affinities are discussed in light of recent paleogenetic studies.